2016
DOI: 10.1002/jbm.b.33667
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt deposition in mineralized bone tissue after metal-on-metal hip resurfacing: Quantitative μ-X-ray-fluorescence analysis of implant material incorporation in periprosthetic tissue

Abstract: Most resurfacing systems are manufactured from cobalt-chromium alloys with metal-on-metal (MoM) bearing couples. Because the quantity of particulate metal and corrosion products which can be released into the periprosthetic milieu is greater in MoM bearings than in metal-on-polyethylene (MoP) bearings, it is hypothesized that the quantity and distribution of debris released by the MoM components induce a compositional change in the periprosthetic bone. To determine the validity of this claim, nondestructive µ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[41] Studies investigating the Co and Cr content in mineralized matrix in femoral heads collected at revision surgery of hip resurfacing implants identified an increase of the Co content in periimplant bone and a correlation of the Co content with implant life time. [42,43] This is interesting since these hip resurfacing implants are known to cause osteolytic lesions at higher prevalence if compared to other hip implant designs. [5,44] Moreover, there is evidence that dissolved Co interacts with type I collagen, the principle protein in bone, by binding to collagen fibrils leading to diminished collagen density.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Studies investigating the Co and Cr content in mineralized matrix in femoral heads collected at revision surgery of hip resurfacing implants identified an increase of the Co content in periimplant bone and a correlation of the Co content with implant life time. [42,43] This is interesting since these hip resurfacing implants are known to cause osteolytic lesions at higher prevalence if compared to other hip implant designs. [5,44] Moreover, there is evidence that dissolved Co interacts with type I collagen, the principle protein in bone, by binding to collagen fibrils leading to diminished collagen density.…”
Section: Discussionmentioning
confidence: 99%
“…While Ti deposition from prostheses was not detected in bone and muscle, Ti from dental implants was found in the jawbone and surrounding soft tissue. 95 Evidence of Ti retention in bone is also found in an animal trial. 98 Bone and muscle serve as the primary accumulation sites for Al, with 60% and 10%, respectively.…”
Section: Metabolism Profiles Of the Prosthetic Metalsmentioning
confidence: 83%
“…Concentration of Co up to 380 ppm was detected in the mineralized periprosthetic bone two years after implantation of the prosthesis. 95 In an animal trial, Co distribution in muscle was also observed. 96 Although the Cr level in the mineralized periprosthetic bone exhibited no significant change, 95 a biokinetic investigation provided evidence of Cr distribution in bone.…”
Section: Metabolism Profiles Of the Prosthetic Metalsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results reported by Hahn et al [79] emphasized the distinction between the effects of MoM and MoP implants. Studies of 13 undecalcified femoral heads which had undergone surface replacement showed increases in cobalt concentrations, up to 380 µg g -1 , compared to control specimens without an implant or with MoP implants.…”
Section: Hip and Knee Implantsmentioning
confidence: 93%